Big data dashboards as smart decision support tools for i-cities – An experiment on stockholm. (February 2018) - Kourtit, Karima; Nijkamp, Peter
Highlights: The paper highlights new trends in smart decision support tools for cities in combination with big data. It offers a systematic big data foundation for interactive policy dashboards for a smart city. Operational i- dashboards support governance of complex urban dynamics in terms of functionalities and land use. The paper illustrates the usefulness of i- dashboards as a navigation tool for effective decisions of stakeholders. Abstract: This study addresses the strategic governance challenges of modern smart cities from the new viewpoint of big data management. It seeks to develop and highlight a systematic methodological framework for handling multivariate big data in a smart urban decision support context in the ' New Urban World ', so as to enhance the cities' competitive performance through the design and development of operational urban management principles and strategies. The specific aim of this paper is to provide the critical and basic cornerstones for an applicable interactive dashboard architecture as a supporting tool in a structured process of innovative city strategies and consequent enhanced socio-economic performance. A core element in the present paper is formed by a smart urban dashboard system that acts as an interactive navigation tool supporting operational choices of all stakeholders involved. This dashboard is able to integrate complex and ever-changing big data bases serving as 'signposts' of city intelligence (or i -city smartness) for daily or strategic decisions of all urban stakeholders. This study thus outlines successively the concept of smart i -cities in our ' urban century ', the great potential of digital technology for managing big data in governing i -cities, and the foundations of an urban dashboard on the basis of the so-called Pentagon model as a policy strategy vehicle. Starting from extensive data on a broad set of global cities, the potential of this approach is exemplified by means of an illustrative application of a smart urban dashboard for the city of Stockholm.